A prospective study of sequential hepatic vein embolization after portal vein embolization in patients scheduled for right‐sided major hepatectomy: Results of feasibility and surgical strategy using functional liver assessment. (6th July 2022) - Araki, Kenichiro; Shibuya, Kei; Harimoto, Norifumi; Watanabe, Akira; Tsukagoshi, Mariko; Ishii, Norihiro; Ikota, Hayato; Yokobori, Takehiko; Tsushima, Yoshito; Shirabe, Ken
Abstract: Background: Hepatic vein embolization (HVE) added to portal vein embolization (PVE) can further increase future remnant liver volume (FRLV) compared with PVE alone. This study was aimed to evaluate feasibility of sequential HVE in a prospective trial and to verify surgical strategy using functional FRLV (fFRLV). Methods: Hepatic vein embolization was prospectively indicated for post‐PVE patients scheduled for right‐sided major hepatectomy if the resection limit of fFRLV using EOB‐magnetic resonance imaging was not satisfied. The resection limit was fFRLV: 615 mL/m 2 for predicting post‐hepatectomy liver failure. Patients who underwent sequential PVE‐HVE (n = 12) were compared with those who underwent PVE alone (n = 31). Results: All patients underwent HVE with no severe complications. Median fFRLV increased from 396 (range: 251‐581) to 634 (range: 422‐740) mL/m 2 by sequential PVE‐HVE. From PVE to HVE, both of FRLV ( P < .001) and fFRLV ( P = .005) significantly increased. The increased width of fFRLV was larger than that of FRLV after performing HVE. Median growth rate was 71.3 (range: 33.3‐80.3) %, which was higher than that of PVE alone (27.0%, range: 6.0‐78.0). All‐cohort resection rate was 88.3%. Strategy of using fFRLV for the resection limit and performing HVE in patients with insufficient functional volume resulted in no liver failure in all patients who underwent hepatectomy. Conclusions: Sequential HVE after PVE is feasible and safe, and HVE induced possibility of further liver growth and its functional improvement. Our surgical strategy using fFRLV may be justified. Abstract : Araki and colleagues report that, compared with portal vein embolization (PVE) alone, sequential hepatic vein embolization (HVE) after PVE induced further growth both in future liver volume and functional future liver volume (fFRLV) on EOB‐MRI. Assessment of fFRLV to determine the need for HVE resulted in high resection rates and no liver failure.